Indentation fracture toughness and surface flaw analysis of sintered alumina/SiC nanocomposites - Anya, C; Roberts, S (1996)
The fracture toughness (K1c) of pressureless-sintered monolithic α-alumina and its composites with 5, 10 and 15 vol% SiC nano-sized particles was investigated using Vickers indentation and a new Hertzian (ball) indentation technique. Both methods showed that the fracture toughness of the composites is better than that of alumina, although the results from the Vickers indentations were complicated by a change in crack geometry from median/radial (alumina) to Palmqvist (composites) An analysis of the number and size of surface flaws using the Hertzian test indicates that, for the same polishing treatment, the composites have a better surface finish. © 1996 Elsevier Science Limited.